A Return to Senses: The Healthy Self in Nadine Gordimer’s Writings - Caraivan Luiza Maria (Romanian Journal of English Studies, 2012)
The paper analyses some aspects of healthy and diseased bodies presented in Nadine Gordimer’s latest writings that mark the writer’s return to senses. Some of Susan Sontag’s considerations on‘illness and its metaphors’ are introduced in order to accentuate the significance of the healing proces in the circle of health, disease and recovery.